Familial clustering of bicuspid aortic valve and its relationship with aortic dilation in first-degree relatives - Galian-Gay, Laura; Carro Hevia, Amelia; Teixido-Turà, Gisela; Rodríguez Palomares, José; Gutiérrez-Moreno, Laura; Maldonado, Giuliana; Gonzàlez-Alujas, María Teresa; Sao-Aviles, Augusto; Gallego, Pastora; Calvo-Iglesias, Francisco; Bermejo, Javier; Robledo-Carmona, Juan; et al. (Heart (British Cardiac Society), 2019)
ObjectiveBicuspid aortic valve (BAV) is the most common congenital heart disease. This study aimed to determine the prevalence rate of BAV in first-degree relatives (FDR) and the inheritance pattern according to different morphotypes and aortic dilation.MethodsBAV probands were consecutively studied at eight tertiary referral centres. After sequential screening, FDR were included in the study. The BAV morphotype, aortic dilation and aortic phenotype were assessed by transthoracic echocardiography.ResultsSeven hundred and twenty-four FDR of 256 BAV probands agreed to undergo family screening. The prevalence of BAV was 6.4% in FDR (9.2% in men, 3.5% in women, p=0.002). Aortic dilation was diagnosed in 9.6% of FRD with tricuspid aortic valves (TAV), with a root phenotype in 2.7% and tubular in 6.9% and more frequently in the presence of arterial hypertension (OR 4.48; CI 95% 2.51 to 7.99; p=0.0001) and valvular regurgitation (OR 5.87, CI 95% 1.37 to 25.16; p=0.025). The heritability (h2 ) of BAV was highly significant (0.47; p=0.002); however, no concordance was observed among valve morphotypes. Aortic dilation heritability was not significant.ConclusionsThe BAV prevalence rate in FDR was low (6.4%) but aortic dilation was observed in 9.6% of FDR with TAV. The heritability of BAV was high without concordance in valve morphotypes, and aortic dilation heritability was not observed. Patients with BAV should be made aware of its familial pattern.